The Influence Of Brand Image And Brand Equity On Customer Satisfaction Of Wardah Cosmetic Products In Bandar Lampung City - Triana Rospita Andharilla; Dorothy Rouly Haratua Pandjaitan (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to examine the influence of brand image and brand equity on customer satisfaction of Wardah cosmetic products in Bandar Lampung City. The research employed a quantitative approach using a survey method, with data collected through questionnaires distributed to 110 respondents. Data analysis was conducted using multiple linear regression and partial tests (t-test) to test the proposed hypotheses. The results indicate that the first hypothesis (H1) is supported, meaning that brand image has a positive and significant effect on customer satisfaction. This suggests that the better Wardah’s brand image is perceived by consumers, the higher their satisfaction level will be. Furthermore, the second hypothesis (H2) is also supported, meaning that brand equity has a positive and significant effect on customer satisfaction. In other words, Wardah’s brand equity such as customer loyalty, brand awareness, and perceived quality contributes to strengthening customer satisfaction. The questionnaire results highlight that the corporate image indicator within the brand image variable requires more attention, as it obtained the lowest average score. Within the brand equity variable, brand loyalty also needs to be improved to enhance customer satisfaction. Improvements in these indicators are expected to significantly increase customer satisfaction and strengthen Wardah’s position in the domestic cosmetics market.